Theoretical aspects of management of finance at the enterprise (Journal of Economic Research & Business Administration, 2016)
In crisis conditions of development of Kazakhstan economy it is nec-essary to introduce modern methods of production management with its financial activity to domestic business. The matter is considered from two points. On the one hand, it is considered as formation of optimum struc-ture of financial management of the enterprise which includes various lev-els of management with accurately regulated functions and duties. On the other hand, it is viewed as the process consisting of the interconnected stages which is directed on achievement of long-term goals. In general, the integrated approach to the solution of the matter allowed to develop the scheme of management of financial resources of the enterprise which is di-rected on effective accumulation and redistribution of financial resources which not only promote maximizing profit and growth of its investment appeal, but also provide stability of a financial position of the enterprise from a position of liquidity and stability.
Keywords: financial activity; financial resources; control system of finance; financial policy; financial strategy; financial tactics of the enter-prise.